Exploring Feasible Carbon Trading Scheme via Graph-Theoretic Method - Bing Shen How; Adeline Shu Ting Tan; Kathleen B. Aviso; Maria Victoria Migo-Sumagang; Viknesh Andiappan; Raymond R. Tan (Chemical Engineering Transactions)
Carbon trading is a mechanism that allows entities to sell or purchase credits which indicate the right to emit carbon dioxide. This strategy is intended to incentivize industrial reduction of carbon emissions and allow firms to outsource decarbonization if internal measures are not viable. The credits are deemed retired after it has been redeemed by a given entity. The feasible trading schemes are constrained by two parameters: (i) temporal availability of carbon credits and (ii) temporal demand of carbon credits. In this work, P-graph – a graph-theoretic framework – is employed to generate optimal trading schemes. The P-graph model is constructed in the form of a cascade model, with the aim of minimizing two critical cost aspects simultaneously: the carbon penalty incurred by the consumers due to non-compliance with emissions goal (at the above-pinch region) and profit loss experienced by the supplier stemming from the costs associated with generating credits (at the below pinch region). The effectiveness of the proposed Carbon Trading P-graph (C_Trading P-graph) is demonstrated through illustrative case studies. This model aids in informed decision-making, facilitating strategic planning in the carbon credit market.